THE IMPACT OF USING JOINT EXTERNAL AUDITING ON THE QUALITY OF FINANCIAL REPORTS IN BANKS LISTED ON THE IRAQ STOCK EXCHANGE - Ahmed Saad Sultan Alsadoan; Prof. Dr. Aida Abdel Kamoun Al-Mowali (Scholar Express Journals, 2025)
In recent years, the global economy has faced several instances of managerial failure and organizational performance collapses, leading to significant financial crises. Investors were affected by the loss of their investments, and many employees lost their jobs. Financial scandals recurred, along with the collapse of major companies in Europe, which also led to the downfall of large auditing firms due to a lack of transparency. In an effort to restore confidence in the accounting and auditing profession, stakeholders have initiated efforts to enhance trust in this field, and the idea of joint auditing was proposed to address issues arising from financial crises and collapses. The research concluded that the researcher was able to prove the research hypothesis, finding a correlation and impact between joint external auditing and the quality of financial reports for the research sample. The distribution of work between the two firms enhances the independence of the auditors, making it difficult for the client to exert pressure on both firms simultaneously while adhering to governance principles and their implementation, which positively reflects on the quality of financial reports.
Keywords: Joint external auditing; quality of financial reports; relationship between joint auditing and quality of statements